2014
DOI: 10.3389/fnins.2014.00256
|View full text |Cite
|
Sign up to set email alerts
|

50 years of hormonal contraception—time to find out, what it does to our brain

Abstract: Hormonal contraceptives are on the market for more than 50 years and used by 100 million women worldwide. However, while endogenous steroids have been convincingly associated with change in brain structure, function and cognitive performance, the effects of synthetic steroids contained in hormonal contraceptives on brain and cognition have barely been investigated. In this article we summarize the sparse findings, describing brain structural, functional and behavioral findings from the literature and suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 56 publications
2
87
2
Order By: Relevance
“…It might be the case that previous OC use permanently affects brain structure and function (Pletzer and Kerschbaum 2014) and that the effect of OCs on economic preferences therefore differs between "never users" and previous users. Relatedly, one reason for discontinuation of using OCs is mood symptoms, and it is possible that users who previously experienced mood symptoms show different effects of OCs (Gingnell et al 2013).…”
Section: Main Results and Robustnessmentioning
confidence: 99%
“…It might be the case that previous OC use permanently affects brain structure and function (Pletzer and Kerschbaum 2014) and that the effect of OCs on economic preferences therefore differs between "never users" and previous users. Relatedly, one reason for discontinuation of using OCs is mood symptoms, and it is possible that users who previously experienced mood symptoms show different effects of OCs (Gingnell et al 2013).…”
Section: Main Results and Robustnessmentioning
confidence: 99%
“…There is particular inconsistency regarding sex differences in brain structure and function, and this has been suggested to reflect the relatively small samples studied (Beltz et al, 2013). But, given that the samples are often ones of convenience (particularly university students) and the high rates of OC use among young adults, it is possible that some inconsistencies reflect an attenuation of sex differences due to the presence of OC users (see also Pletzer and Kerschbaum, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…Such work was not mentioned in the 1998 special issue on estrogens and cognition in Hormones and Behavior (see Williams, 1998) nor in a recent review of estrogens and cognition (Luine, 2014). But, the past year has seen three papers reviewing research on the cognitive effects of OCs, and all highlight the need for future research in this area (Gogos et al, 2014;Pletzer and Kerschbaum, 2014;Warren et al, 2014). Before discussing evidence to date, we consider some information on OCs that is relevant to understanding how they might affect cognition.…”
mentioning
confidence: 94%
“…A PET study of asymptomatic women showed decreased activation of the dorsolateral prefrontal cortex, inferior parietal lobule, and posterior inferior temporal cortex during leuprolide-induced hypogonadism, whereas the expected pattern of cortical activity returned following either estradiol or progesterone add-back (23). Studies of the effects of combined oral contraceptives have identified increased activity in the medial prefrontal cortex, ACC, dorsolateral prefrontal cortex, and inferior frontal gyrus (1,239,263), and decreased activity in posterior cingulate cortex, medial frontal gyrus, inferior frontal gyrus, and insula (1,109).…”
Section: Network Neuroscience: Reproductive Steroids Regulate the Neumentioning
confidence: 99%